دور العلاقات العامة و أهميتها في الترويج السياحي - خليفي, مريم; غزلان, فاطمة الزهراء (University of eloued جامعة الوادي, 2018)
Tourism is a sophisticated social and cultural phenomenon , The tourism process is an important type of humanitarian activity There have been numerous and advanced research and studies. Promised tourist concepts of phenomena, Which characterized the twentieth century , And stretched their threads to achieve successes To attract increasing numbers of tourists And positively reflected on the movement of communities, The most populated of tourist activity. Tourism promotion is one of the elements of tourism marketing mix, But the success of any tourism program depends on the ability of the company But the success of any tourist program depends on the ability of the tourist company To promote any program, Thus achieving the established goal, To attract as many tourists as possible to visit the place promoted, One element of tourism promotion is public relations. The latter play critical and important roles in the success of the heart and mind of a conscious and scientific plan, We mean public relations, which undertake to contribute to research and studies And provide proposals that create the appropriate areas, conditions and conditions for tourists. Although tourism public relations is an element of tourism promotion , But it has a major and important task It is a counter-feeding to tourism promotion
مذكرة ماستر تسويق فندقي وسياحي
Keywords: السياحة ، الترويج السياحي ، العلاقات العامة